KEEFEKTIFAN MODEL PEMBELAJARAN THREE STEP INTERVIEW BERBASIS SCIENTIFIC TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII MATERI BANGUN RUANG SISI - Maftuhatus Sholihah; Venissa Dian Mawarsari; Martyana Prihaswati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to determine the effectiveness of Three Step Interviewbased Scientific learning model to ability of mathematical communication. This research is an experimental research conducted at SMP Negeri 2 Ngadirejo in Temanggung District.Sampling with Purposive Sampling technique. The research population is all students of class VIII with sample of class VIII B (experiment) and class VIII C (control). The independent variable used is motivation and communicative, the dependent variable of mathematical communication ability. Methods of data collection using interviews, documentation, tests, observations, and questionnaires. The results showed: (1) the average mathematical communication ability of the experimental class students reached 83.24 with the percentage of completeness of 79.411%; (2) there was a motivationand communicative influence on the mathematical communication ability 80.4%;(3) there is difference of experiment class average which reach 83,24 and control class reach 73,76. Based on the three criteria above shows that Three Step Interviewbased Scientific learning model to the mathematical communication ability of grade VIII students of building the flatside space effective.Keywords: Three Step Interview, Scientific, Mathematical Communication.